Adolescents' reflections on school-based alcohol education in the United Kingdom: education as usual compared with a structured harm reduction intervention. (1st November 2016) - Harvey, Séamus A.; McKay, Michael T.; Sumnall, Harry R.
Abstract: Alcohol consumption by adolescents in the United Kingdom (UK) remains high. School-based interventions are expected to play a key role in preventing adolescent alcohol consumption. A series of focus groups were conducted with pupils who received alcohol education as usual and pupils who received a Northern Ireland adaptation of the School Health and Alcohol Harm Reduction Project (SHAHRP), a universal alcohol education program designed to reduce the harms experienced by young drinkers. This study sought to compare and contrast the participants' engagement with and enjoyment of the different alcohol education that they had received. Focus groups were completed with 129 pupils in 16 schools in Northern Ireland and Scotland. Alcohol education as usual was viewed negatively and was regarded as unstructured, boring, repetitive, and unrealistic. In contrast, the adaptation of SHAHRP was viewed positively and was regarded as enjoyable and worthwhile, and engaging and relevant to the participants' experiences of alcohol use. These findings suggest that one reason why alcohol education as usual may not be successful in preventing adolescent drinking and protecting adolescents from negative outcomes may be due to its failure to engage participants. Higher acceptability by pupils means that the adaptation of SHAHRP may be one viable alternative.